Improving smoking cessation care in pregnancy at Aboriginal Medical Services: 'ICAN QUIT in Pregnancy' step-wedge cluster randomised study. Issue 6 (4th June 2019) - Bar-Zeev, Yael; Bovill, Michelle; Bonevski, Billie; Gruppetta, Maree; Oldmeadow, Christopher; Palazzi, Kerrin; Atkins, Louise; Reath, Jennifer; Gould, Gillian Sandra
Abstract : Objectives: This study aimed to examine the impact of the 'ICAN QUIT in Pregnancy' intervention on individual health providers (HPs) smoking cessation care (SCC) knowledge, attitudes and practices in general, and specifically regarding nicotine replacement therapy (NRT) prescription. Design: Step-wedge clustered randomised controlled study. HPs answered a preintervention and 1–6 months postintervention survey. Setting: Six Aboriginal Medical Services (AMSs) in three states of Australia. Participants: All HPs were invited to participate. Of 93 eligible, 50 consented (54%), 45 completed the presurvey (90%) and 20 the post (40%). Intervention: Included three 1-hour webinar sessions, educational resource package and free oral NRT. Outcomes: HPs knowledge was measured using two composite scores—one from all 24 true/false statements, and one from 12 NRT-specific statements. Self-assessment of 22 attitudes to providing SCC were measured using a five-point Likert scale (Strongly disagree to Strongly agree). Two composite mean scores were calculated—one for 15 general SCC attitudes, and one for 7 NRT-specific attitudes. Self-reported provision of SCC components was measured on a five-point Likert scale (Never to Always). Feasibility outcomes, and data collected on the service and patient level are reported elsewhere. Results: Mean knowledge composite scores improved from pre to post (78% vs 84% correct, difference 5.95, 95% CI 1.57 to 10.32). Mean NRT-specific knowledge composite score also improved (68% vs 79% correct, difference 9.9, 95% CI 3.66 to 16.14). Mean attitude composite score improved (3.65 (SD 0.4) to 3.87 (SD 0.4), difference 0.23, 95% CI 0.05 to 0.41). Mean NRT-specific attitudes composite score also improved (3.37 (SD 0.6) to 3.64 (SD 0.7), difference 0.36, 95% CI 0.13 to 0.6). Self-reported practices were unchanged, including prescribing NRT. Conclusions: A multicomponent culturally sensitive intervention in AMSs was feasible, and might improve HPs provision of SCC to pregnant Aboriginal women. Changes in NRT prescription rates may require additional intensive measures. Trial registration number: ACTRN 12616001603404; Results.